Semantic web services: state of the art - Lanthaler, M.; Granitzer, M.; Guetl, Christian (IADIS Press, 2010)
Service-oriented architectures (SOA) built on Web services were a first attempt to streamline and automate business processes in order to increase productivity but the utopian promise of uniform service interface standards, metadata, and universal service registries, in the form of the SOAP, WSDL and UDDI standards has proven elusive. Furthermore, the RPC-oriented model of those traditional Web services is not Web-friendly. Thus more and more prominent Web service providers opted to expose their services based on the REST architectural style. Nevertheless there are still problems on formal describing, finding, and orchestrating RESTful services. While there are already a number of different approaches none so far has managed to break out of its academic confines. This paper focuses on an extensive survey comparing the existing state-of-the-art technologies for semantically annotated Web services as a first step towards a proposal designed specifically for RESTful services.